2007
DOI: 10.1111/j.1365-2222.2007.02849.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal breast‐milk and intestinal bifidobacteria guide the compositional development of the Bifidobacterium microbiota in infants at risk of allergic disease

Abstract: Breast-milk contains significant numbers of bifidobacteria and the maternal allergic status further deranges the counts of bifidobacteria in breast-milk. Maternal fecal and breast-milk bifidobacterial counts impacted on the infants' fecal Bifidobacterium levels. Breast-milk bacteria should thus be considered an important source of bacteria in the establishment of infantile intestinal microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
163
1
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(189 citation statements)
references
References 57 publications
14
163
1
11
Order By: Relevance
“…Lower abundance of Bifidobacterium spp. has been reported in mothers with atopic disease compared to those observed in healthy mother (23).…”
Section: Breast Milk As the Link Between Mother And Infantmentioning
confidence: 96%
See 1 more Smart Citation
“…Lower abundance of Bifidobacterium spp. has been reported in mothers with atopic disease compared to those observed in healthy mother (23).…”
Section: Breast Milk As the Link Between Mother And Infantmentioning
confidence: 96%
“…In addition, maternal health including conditions such as allergy and obesity may affect milk microbiota, resulting in reduced levels of Bifidobacterium spp. compared to healthy mothers (22,23).…”
Section: Microbial Exposure In Uteromentioning
confidence: 99%
“…65 Both Hunt et al 64 and Cabrera-Rubio et al 65 only detected few sequences of Bifidobacterium upon analysis of milk samples. However, other studies have identified this genus in over 90% of samples taken from mothers 61 and have found associations between levels of bifidobacteria in maternal milk and infant feces, 66 which may partly explain the increased levels of Bifidobacterium found in the feces of BF infants. Although taxonomic differences could be attributed to primers used for analysis, as mentioned previously, incomplete cell lysis during DNA isolation, due to the thick bacterial cell wall, has been recognized to influence the ability to detect bifidobacteria in samples.…”
Section: Human Milk Microbiotamentioning
confidence: 97%
“…35 The infant microbiota are also established from bacteria such as Bifidobacterium and Lactobacillus found in human milk. 36,37 The high concentration of galactooligosaccharides in human milk provides optimal growth conditions for bifidobacteria species, which are prevalent microbes in the infant's intestinal microbiome. 38,39 We now appreciate that reduction of nitrate to nitrite requires the commensal bacteria that normally reside in our body.…”
Section: Discussionmentioning
confidence: 99%